The use of virtual reality in table tennis training: a comparison of selected muscle activation in upper limbs during strokes in virtual reality and normal environments - Skopek, M.; Heidler, J.; Hnizdil, J.; Kresta, J.; Vysocka, K. (Journal of Physical Education and Sport, 2023)
The objective of this study was to assess the level of agreement between muscle involvement in the upper limbs of table tennis players during training in virtual reality (VR) versus a normal training environment. The research was conducted on an intentionally selected sample of 8 female probands who actively compete in a table tennis league. We monitored the activity of four selected upper limb muscles (biceps brachii, extensor carpi ulnaris, flexor carpi radialis, and posterior deltoid) during two basic strokes (backhand and forehand topspin). The study assesses the overall muscle activation in two different environments: a regular training environment and VR. To obtain data during two basic strokes (backhand and forehand topspin), we utilized a device (Noraxon) that measures and evaluates muscle activation using surface electromyography posterior. For the VR training environment, we employed the Eleven Table Tennis program with the head-mounted display HTC Vive Pro Eye. On the other hand, the regular training environment involved the use of a Joola Table Tennis Buddy Pro robotic ball feeder. The results showed that the total muscle activation of the selected muscles varied significantly between the two environments (regular training versus VR). Specifically, for selected muscles there was a notably higher muscle load when playing in the regular environment compared to VR. Based on these findings, we recommend using the virtual environment for training only for beginners or for casual table tennis playing. For performance-level players, VR is not a suitable training tool in terms of muscle activation.